New insights into the clinical and molecular spectrum of the novel CYFIP2-related neurodevelopmental disorder and impairment of the WRC-mediated actin dynamics - Begemann, Anaïs; Sticht, Heinrich; Begtrup, Amber; Vitobello, Antonio; Faivre, Laurence; Banka, Siddharth; Alhaddad, Bader; Asadollahi, Reza; Becker, Jessica; Bierhals, Tatjana; Brown, Kathleen E.; Bruel, Ange-Line; et al. (Genetics in medicine, 2021)
Purpose - A few de novo missense variants in the cytoplasmic FMRP-interacting protein 2 (CYFIP2) gene have recently been described as a novel cause of severe intellectual disability, seizures, and hypotonia in 18 individuals, with p.Arg87 substitutions in the majority. - Methods - We assembled data from 19 newly identified and all 18 previously published individuals with CYFIP2 variants. By structural modeling and investigation of WAVE-regulatory complex (WRC)-mediated actin polymerization in six patient fibroblast lines we assessed the impact of CYFIP2 variants on the WRC. - Results - Sixteen of 19 individuals harbor two previously described and 11 novel (likely) disease-associated missense variants. We report p.Asp724 as second mutational hotspot (4/19 cases). Genotype-phenotype correlation confirms a consistently severe phenotype in p.Arg87 patients but a more variable phenotype in p.Asp724 and other substitutions. Three individuals with milder phenotypes carry putative loss-of-function variants, which remain of unclear pathogenicity. Structural modeling predicted missense variants to disturb interactions within the WRC or impair CYFIP2 stability. Consistent with its role in WRC-mediated actin polymerization we substantiate aberrant regulation of the actin cytoskeleton in patient fibroblasts. - Conclusion - Our study expands the clinical and molecular spectrum of CYFIP2-related neurodevelopmental disorder and provides evidence for aberrant WRC-mediated actin dynamics as contributing cellular pathomechanism.
Online veröffentlicht: 5. November 2020
Gesehen am 15.05.2024